A high-flatness stainless steel strip for automobile decoration and its preparation process

A process for preparing a highly flat stainless steel strip for automobile decoration, involving laser cladding and ion nitrocarburizing, followed by a self-healing emulsion and composite silica coating, addresses wear and corrosion issues, enhancing durability and longevity.

CN118847478BActive Publication Date: 2024-12-17JIANGSU YONGJIN METAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411311630.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-17
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

Existing stainless steel strips used for automobile decoration suffer from poor wear resistance, limited flatness, and corrosion, which reduces their service life.

Method used

A process involving the preparation of stainless steel strips involves hot rolling, annealing, pickling, rolling, flattening, and finishing stainless steel strips, followed by laser cladding high entropy alloy layers, and ion nitrocarburizing stainless steel strips, and applying a protective coating made from a self-healing emulsion and composite silica to enhance wear and corrosion resistance.

Benefits of technology

The process results in a highly flat, wear-resistant, and corrosion-resistant stainless steel strip with a self-repairing super-hydrophobic surface, improving mechanical durability and longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of stainless steel, in particular to a high-flatness stainless steel strip for automobile decoration and a preparation process thereof. The laser cladding high entropy alloy layer and ion nitrocarburizing are used to improve the hardness, wear resistance and corrosion resistance of the stainless steel; a protective coating prepared by blending a self-repairing emulsion and composite silica is coated on the surface of the pretreated stainless steel strip; a side chain-containing organic silicon prepolymer is synthesized, dimethylol propionic acid is used as a hydrophilic chain extender, 2,2'-diaminodiphenyl disulfide is used to further extend the chain, hydroxyethyl methacrylate is used as a capping agent, and 1-thioglycerol is grafted on a double-bond terminated polyurethane; particles with different sizes are assembled by chemical bonding through an amino-epoxy reaction to obtain strawberry-shaped silica, and amino groups on the surface of the strawberry-shaped silica are further introduced through an amidation reaction to construct a multi-dimensional hydrophobic silica of micro-nano scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel, in particular to a highly flat stainless steel strip for automobile decoration and a preparation process thereof. Background Art

[0002] Car decoration generally refers to improving the beauty and ornamental value of a car by adding some accessories. The decorations are installed without changing the function and structure of the car itself to meet people's increasingly enhanced personalized needs.

[0003] Stainless steel is more and more widely used in automobile decoration because of its high strength and aging resistance. Most of the existing stainless steel strips used for automobile decoration are austenitic stainless steel strips. Compared with other stainless steels, although they have high mechanical strength, they have poor wear resistance and limited flatness. Wear and corrosion also reduce their service life. Summary of the invention

[0004] The object of the present invention is to provide a highly flat stainless steel strip for automobile decoration and a preparation process thereof, so as to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A preparation process of a highly flat stainless steel strip for automobile decoration comprises the following steps:

[0007] S1: Stainless steel raw materials are put into a vacuum furnace for melting, and hot rolling, annealing, pickling, rolling, flattening and finishing are performed in sequence to form a stainless steel strip;

[0008] S2: FeCoNiCr is selected as the cladding material, and laser cladding treatment is performed to obtain a clad stainless steel strip;

[0009] S3: frosting, polishing, cleaning, and drying the clad stainless steel strip in sequence, and then ion nitrocarburizing, cleaning, and drying to obtain a pretreated stainless steel strip;

[0010] S4: Preparation of protective coating using self-healing emulsion and composite silica;

[0011] S5: coating the protective coating on the surface of the pretreated stainless steel strip to form a protective layer, thereby obtaining a highly flat stainless steel strip for automobile decoration.

[0012] Furthermore, the working conditions of the annealing treatment are: heating to 950° C. and keeping the temperature for 25-35 minutes.

[0013] Furthermore, the working conditions of the laser cladding treatment are: using argon as the powder feeding gas source, the powder feeding amount is 11 g / min, the laser power is 1.2 kW, the scanning speed is 6 mm / s, the circular spot diameter is 3 mm, and the overlap rate is 50%.

[0014] Furthermore, the working conditions of the ion nitrocarburizing treatment are as follows: before heating to 300°C, a mixed gas of argon and methane with a volume ratio of 8:2 is introduced, ammonia is introduced when the temperature is raised from 300°C to 485°C, and ammonia, argon and methane with a volume ratio of 20:8:2 are introduced at 485°C; the holding temperature is 485°C, and the holding time is 5h.

[0015] Furthermore, the mass ratio of the composite silica to the self-healing emulsion in the protective coating is (3-5):55.

[0016] Further, the preparation of the self-repairing emulsion comprises the following steps:

[0017] Under nitrogen protection, polycarbonate diol, hydroxyl-terminated polydimethylsiloxane, N,N-dimethylformamide and dibutyltin dilaurate are mixed, the temperature is raised to 78-82°C, isophorone diisocyanate is added, the temperature is kept for 2-3 hours, a mixed solution of dihydroxymethylpropionic acid and N,N-dimethylformamide is added, the temperature is kept for 2-3 hours, the temperature is lowered to 48-52°C, 2,2'-diaminodiphenyl disulfide and a mixed solution of N,N-dimethylformamide are added, the temperature is kept for 1-2 hours, hydroxyethyl methacrylate is added and the temperature is kept for 2-3 hours, 1-thioglycerol, 2-hydroxy-2-methylpropiophenone and a mixed solution of N,N-dimethylformamide are added, the mixture is treated with ultraviolet irradiation, precipitated in n-hexane for 3-5 times, triethylamine is added, and deionized water is added for emulsification for 1-2 hours to obtain a self-healing emulsion.

[0018] Furthermore, the working conditions of the ultraviolet irradiation treatment are: irradiation under ultraviolet light with a wavelength of 365nm for 3-4h.

[0019] Further, the preparation of composite silicon dioxide comprises the following steps:

[0020] 1) Mix nano-silica, ethanol, ammonia water, deionized water and 3-aminopropyltriethoxysilane, heat to 78-82°C and keep warm for 4-5 hours, wash and dry to obtain amino-modified nano-silica;

[0021] 2) Mix micronized silica, ethanol, ammonia water, deionized water and γ-glycidyloxypropyltrimethoxysilane, heat to 58-62°C and keep warm for 4-5 hours, wash and dry to obtain epoxidized micronized silica;

[0022] 3) Mix amination nano-silica, epoxidized micro-silica, ethanol, ammonia water and deionized water, heat to 98-102°C and keep warm for 7-8 hours, wash and dry to obtain strawberry-shaped silica;

[0023] 4) Mix strawberry-shaped silica and dimethyl sulfoxide, disperse them by ultrasonic for 20-30 min, add a mixed solution of 3-fluoro-4-carboxyphenylboric acid, l-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and dimethyl sulfoxide, keep warm at 18-25° C. for 3-4 h, centrifuge, wash and freeze-dry to obtain composite silica.

[0024] Furthermore, the mass ratio of strawberry-shaped silica, 3-fluoro-4-carboxyphenylboric acid, and N-hydroxysuccinimide is 2.1:0.7:0.8.

[0025] Beneficial effects of the present invention:

[0026] The invention provides a highly flat stainless steel strip for automobile decoration and a preparation process thereof. Through process adjustment and component design, a wear-resistant and corrosion-resistant highly flat stainless steel strip for automobile decoration with a self-repairing super-hydrophobic surface is prepared.

[0027] The present invention adopts laser cladding high entropy alloy layer and ion nitrocarburizing to improve the hardness, wear resistance and corrosion resistance of stainless steel, and obtains a pretreated stainless steel strip with high flatness and good surface density by controlling the process parameters of laser cladding and ion nitrocarburizing.

[0028] In order to give the stainless steel strip excellent resistance to mechanical damage, a protective coating prepared by blending a self-healing emulsion and composite silica is coated on the surface of the pretreated stainless steel strip to construct a super-hydrophobic, wear-resistant and corrosion-resistant protective layer.

[0029] Among them, the self-healing emulsion uses polycarbonate diol, hydroxyl-terminated polydimethylsiloxane, and isophorone diisocyanate as raw materials. Under the action of a catalyst, a side chain-containing silicone prepolymer is synthesized to improve the water resistance and thermal stability of the self-healing emulsion. Dihydroxymethylpropionic acid is used as a hydrophilic chain extender, and 2,2'-diaminodiphenyl disulfide is used to further extend the chain, and a dynamic disulfide bond is introduced to give it self-healing properties. Then, hydroxyethyl methacrylate is used as a capping agent to obtain a double-bond-terminated polyurethane. Then, the photo-click reaction of the thiol-double bond is used to graft 1-thioglycerol on the double-bond-terminated polyurethane to obtain a dihydroxy-terminated polyurethane, which is then emulsified with water to obtain the self-healing emulsion.

[0030] The present invention introduces silicon dioxide with the advantages of stable chemical properties, acid resistance, alkali resistance, high temperature resistance, etc. as a filler for the protective coating. In order to give the protective layer super-hydrophobicity, a super-hydrophobic surface is jointly constructed by constructing a micro-nano multi-scale rough structure and combining low surface energy modification. The nano silicon dioxide is coated and modified by 3-aminopropyltriethoxysilane to obtain amino nano silicon dioxide. The micron silicon dioxide particles are coated and modified by γ-glycidyloxypropyltrimethoxysilane to obtain epoxidized micron silicon dioxide. Through amino-epoxy reaction, particles with different sizes are assembled by chemical bonding to obtain strawberry The strawberry-shaped silica uses the amino groups on the surface of the strawberry-shaped silica to further introduce phenylboronic acid groups and fluorine groups through amidation reaction to construct a micro-nano-scale multidimensional hydrophobic silica, which is introduced into the protective coating to greatly improve the thermal stability and corrosion resistance of the coating; at the same time, the phenylboronic acid groups on the surface of the composite silica can form reversible borate ester bonds with the dihydroxy groups in the dihydroxy-terminated polyurethane, undergo chemical bonding, produce a synergistic effect, and increase the cross-linking density. By controlling the mass ratio of the self-healing emulsion and the composite silica, a complex self-healing network system is constructed, which further improves its self-healing rate and thermal stability, thereby improving the corrosion resistance of the protective layer. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0033] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0034] Embodiment 1: A process for preparing a highly flat stainless steel strip for automobile decoration, comprising the following steps:

[0035] S1: Stainless steel raw materials are put into a vacuum furnace for melting, and hot rolling, annealing, pickling, rolling, flattening and finishing are performed in sequence to form a stainless steel strip;

[0036] The working conditions of annealing treatment are: heating to 950°C and keeping it for 25 min;

[0037] S2: FeCoNiCr is selected as the cladding material, and laser cladding treatment is performed to obtain a clad stainless steel strip;

[0038] The working conditions of laser cladding treatment are as follows: argon gas is used as powder feeding gas source, powder feeding amount is 11g / min, laser power is 1.2kW, scanning speed is 6mm / s, circular spot diameter is 3mm, overlap rate is 50%;

[0039] S3: frosting, polishing, cleaning, and drying the clad stainless steel strip in sequence, and then ion nitrocarburizing, cleaning, and drying to obtain a pretreated stainless steel strip;

[0040] The working conditions of ion nitrocarburizing treatment are as follows: before heating to 300°C, a mixed gas of argon and methane with a volume ratio of 8:2 is introduced, ammonia is introduced when the temperature rises from 300°C to 485°C, and ammonia, argon and methane with a volume ratio of 20:8:2 are introduced at 485°C; the holding temperature is 485°C and the holding time is 5h;

[0041] S4: Preparation of protective coating using self-healing emulsion and composite silica;

[0042] The preparation of the self-healing emulsion includes the following steps:

[0043] Under nitrogen protection, 4g polycarbonate diol, 1.6g hydroxyl-terminated polydimethylsiloxane, 15mL N,N-dimethylformamide, and 2 drops of dibutyltin dilaurate were mixed, the temperature was raised to 78°C, 16g isophorone diisocyanate was added, and the mixture was kept warm for 3h, 0.6g dihydroxymethylpropionic acid and 5mL N,N-dimethylformamide were added, and the mixture was kept warm for 2h, and the temperature was lowered to 48°C and 0.8g 2,2'-diaminodiphenylene glycol was added. thioether, 5mL N, N-dimethylformamide mixture, keep warm for 2h, add 1.5g hydroxyethyl methacrylate and keep warm for 2h, add 1.8g 1-thioglycerol, 0.06g 2-hydroxy-2-methylpropiophenone, 40mL N, N-dimethylformamide mixture, ultraviolet irradiation treatment, precipitate in n-hexane 3 times, add 0.8g triethylamine, add deionized water and emulsify for 1h to obtain a self-healing emulsion with a solid content of 20%;

[0044] The working conditions of the UV irradiation treatment were: irradiation with UV light of wavelength 365 nm for 3 h;

[0045] The preparation of composite silicon dioxide comprises the following steps:

[0046] 1) Mix 5 g of nano-silica, 20 mL of ethanol, 3 mL of ammonia water, 2 mL of deionized water, and 3 g of 3-aminopropyltriethoxysilane, heat to 78 ° C for 5 h, wash, and dry to obtain amino-modified nano-silica;

[0047] 2) Take 5g of micronized silica, 20mL of ethanol, 3mL of ammonia water, 2mL of deionized water, and 3g of γ-glycidyloxypropyltrimethoxysilane, mix them, heat them to 58°C and keep them warm for 5h, wash them with ethanol several times, wash and dry them to obtain epoxidized micronized silica;

[0048] 3) Take 24g of amino-modified nano-silica, 18g of epoxidized micro-silica, 20mL of ethanol, 3mL of ammonia water, and 2mL of deionized water, mix them, heat them to 98°C and keep them warm for 8h, wash and dry them to obtain strawberry-shaped silica;

[0049] 4) 2.1 g of strawberry-shaped silica and 100 mL of dimethyl sulfoxide were mixed, ultrasonically dispersed for 20 min, 0.7 g of 3-fluoro-4-carboxyphenylboronic acid, 2.8 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.8 g of N-hydroxysuccinimide, and 100 mL of dimethyl sulfoxide were added, and the mixture was kept at 18°C ​​for 4 h, centrifuged, washed, and freeze-dried to obtain composite silica;

[0050] The mass ratio of composite silica to self-repairing emulsion in the protective coating is 3:55;

[0051] S5: coating the protective coating on the surface of the pretreated stainless steel strip to form a protective layer, thereby obtaining a highly flat stainless steel strip for automobile decoration.

[0052] Embodiment 2: A process for preparing a highly flat stainless steel strip for automobile decoration, comprising the following steps:

[0053] S1: Stainless steel raw materials are put into a vacuum furnace for melting, and hot rolling, annealing, pickling, rolling, flattening and finishing are performed in sequence to form a stainless steel strip;

[0054] The working conditions of annealing treatment are: heating to 950°C and keeping it for 30 min;

[0055] S2: FeCoNiCr is selected as the cladding material, and laser cladding treatment is performed to obtain a clad stainless steel strip;

[0056] The working conditions of laser cladding treatment are as follows: argon gas is used as powder feeding gas source, powder feeding amount is 11g / min, laser power is 1.2kW, scanning speed is 6mm / s, circular spot diameter is 3mm, overlap rate is 50%;

[0057] S3: frosting, polishing, cleaning, and drying the clad stainless steel strip in sequence, and then ion nitrocarburizing, cleaning, and drying to obtain a pretreated stainless steel strip;

[0058] The working conditions of ion nitrocarburizing treatment are as follows: before heating to 300°C, a mixed gas of argon and methane with a volume ratio of 8:2 is introduced, ammonia is introduced when the temperature rises from 300°C to 485°C, and ammonia, argon and methane with a volume ratio of 20:8:2 are introduced at 485°C; the holding temperature is 485°C and the holding time is 5h;

[0059] S4: Preparation of protective coating using self-healing emulsion and composite silica;

[0060] The preparation of the self-healing emulsion includes the following steps:

[0061] Under nitrogen protection, 4g polycarbonate diol, 1.6g hydroxyl-terminated polydimethylsiloxane, 15mL N,N-dimethylformamide, and 2 drops of dibutyltin dilaurate were mixed, the temperature was raised to 80°C, 16g isophorone diisocyanate was added, and the mixture was kept warm for 2.5h. 0.6g dihydroxymethylpropionic acid and 5mL N,N-dimethylformamide were added, and the mixture was kept warm for 2.5h. The temperature was lowered to 50°C and 0.8g 2,2'-diaminodiphenylene glycol was added. A mixture of thioether and 5 mL of N, N-dimethylformamide was kept warm for 1.5 h, 1.5 g of hydroxyethyl methacrylate was added and kept warm for 2.5 h, 1.8 g of 1-thioglycerol, 0.06 g of 2-hydroxy-2-methylpropiophenone, and 40 mL of N, N-dimethylformamide were added, and the mixture was treated with ultraviolet irradiation, precipitated in n-hexane for 4 times, 0.8 g of triethylamine was added, and deionized water was added for emulsification for 1 h to obtain a self-healing emulsion with a solid content of 20%;

[0062] The working conditions of the UV irradiation treatment were: irradiation with UV light of wavelength 365 nm for 3.5 h;

[0063] The preparation of composite silicon dioxide comprises the following steps:

[0064] 1) Mix 5 g of nano-silica, 20 mL of ethanol, 3 mL of ammonia water, 2 mL of deionized water, and 3 g of 3-aminopropyltriethoxysilane, heat to 80 ° C and keep warm for 4.5 h, wash and dry to obtain amino-modified nano-silica;

[0065] 2) Mix 5g of micronized silica, 20mL of ethanol, 3mL of ammonia water, 2mL of deionized water, and 3g of γ-glycidyloxypropyltrimethoxysilane, heat to 60°C and keep warm for 4.5h, wash with ethanol several times, wash and dry to obtain epoxidized micronized silica;

[0066] 3) Take 24g of amino-modified nano-silica, 18g of epoxidized micro-silica, 20mL of ethanol, 3mL of ammonia water, and 2mL of deionized water, mix them, heat them to 100°C and keep them warm for 7.5h, wash and dry them to obtain strawberry-shaped silica;

[0067] 4) 2.1 g of strawberry-shaped silica and 100 mL of dimethyl sulfoxide were mixed, ultrasonically dispersed for 25 min, 0.7 g of 3-fluoro-4-carboxyphenylboronic acid, 2.8 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.8 g of N-hydroxysuccinimide, and 100 mL of dimethyl sulfoxide were added, and the mixture was kept at 20 ° C for 3.5 h, centrifuged, washed, and freeze-dried to obtain composite silica;

[0068] The mass ratio of composite silica to self-repairing emulsion in the protective coating is 4:55;

[0069] S5: coating the protective coating on the surface of the pretreated stainless steel strip to form a protective layer, thereby obtaining a highly flat stainless steel strip for automobile decoration.

[0070] Embodiment 3: A process for preparing a highly flat stainless steel strip for automobile decoration, comprising the following steps:

[0071] S1: Stainless steel raw materials are put into a vacuum furnace for melting, and hot rolling, annealing, pickling, rolling, flattening and finishing are performed in sequence to form a stainless steel strip;

[0072] The working conditions of annealing treatment are: heating to 950°C and keeping it for 35 min;

[0073] S2: FeCoNiCr is selected as the cladding material, and laser cladding treatment is performed to obtain a clad stainless steel strip;

[0074] The working conditions of laser cladding treatment are as follows: argon gas is used as powder feeding gas source, powder feeding amount is 11g / min, laser power is 1.2kW, scanning speed is 6mm / s, circular spot diameter is 3mm, overlap rate is 50%;

[0075] S3: frosting, polishing, cleaning, and drying the clad stainless steel strip in sequence, and then ion nitrocarburizing, cleaning, and drying to obtain a pretreated stainless steel strip;

[0076] The working conditions of ion nitrocarburizing treatment are as follows: before heating to 300°C, a mixed gas of argon and methane with a volume ratio of 8:2 is introduced, ammonia is introduced when the temperature rises from 300°C to 485°C, and ammonia, argon and methane with a volume ratio of 20:8:2 are introduced at 485°C; the holding temperature is 485°C and the holding time is 5h;

[0077] S4: Preparation of protective coating using self-healing emulsion and composite silica;

[0078] The preparation of the self-healing emulsion includes the following steps:

[0079] Under nitrogen protection, 4g polycarbonate diol, 1.6g hydroxyl-terminated polydimethylsiloxane, 15mL N,N-dimethylformamide, and 2 drops of dibutyltin dilaurate were mixed, the temperature was raised to 82°C, 16g isophorone diisocyanate was added, and the mixture was kept warm for 2h, 0.6g dihydroxymethylpropionic acid and 5mL N,N-dimethylformamide were added, and the mixture was kept warm for 3h, and the temperature was lowered to 52°C and 0.8g 2,2'-diaminodiphenylene glycol was added. A mixture of thioether and 5 mL of N, N-dimethylformamide was kept warm for 1 hour, 1.5 g of hydroxyethyl methacrylate was added and kept warm for 3 hours, 1.8 g of 1-thioglycerol, 0.06 g of 2-hydroxy-2-methylpropiophenone, and 40 mL of N, N-dimethylformamide were added, and the mixture was treated with ultraviolet irradiation, precipitated in n-hexane for 5 times, 0.8 g of triethylamine was added, and deionized water was added for emulsification for 1 hour to obtain a self-healing emulsion with a solid content of 20%;

[0080] The working conditions of UV irradiation treatment were: irradiation under UV light with a wavelength of 365 nm for 4 h;

[0081] The preparation of composite silicon dioxide comprises the following steps:

[0082] 1) Mix 5 g of nano-silica, 20 mL of ethanol, 3 mL of ammonia water, 2 mL of deionized water, and 3 g of 3-aminopropyltriethoxysilane, heat to 82 °C and keep warm for 4 h, wash and dry to obtain amino-modified nano-silica;

[0083] 2) Take 5g of micronized silica, 20mL of ethanol, 3mL of ammonia water, 2mL of deionized water, and 3g of γ-glycidyloxypropyltrimethoxysilane, mix them, heat them to 62°C and keep them warm for 4h, wash them with ethanol several times, wash and dry them to obtain epoxidized micronized silica;

[0084] 3) Take 24g of amino-modified nano-silica, 18g of epoxidized micro-silica, 20mL of ethanol, 3mL of ammonia water, and 2mL of deionized water, mix them, heat them to 102°C and keep them warm for 7h, wash and dry them to obtain strawberry-shaped silica;

[0085] 4) 2.1 g of strawberry-shaped silica and 100 mL of dimethyl sulfoxide were mixed, ultrasonically dispersed for 20-30 min, 0.7 g of 3-fluoro-4-carboxyphenylboronic acid, 2.8 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.8 g of N-hydroxysuccinimide, and 100 mL of dimethyl sulfoxide were added, and the mixture was kept at 25 ° C for 3 h, centrifuged, washed, and freeze-dried to obtain composite silica;

[0086] The mass ratio of composite silica to self-repairing emulsion in the protective coating is 5:55;

[0087] S5: coating the protective coating on the surface of the pretreated stainless steel strip to form a protective layer, thereby obtaining a highly flat stainless steel strip for automobile decoration.

[0088] Comparative Example 1: Taking Example 3 as the control group, the composite silica was replaced with strawberry-shaped silica, and the other processes were normal.

[0089] Comparative Example 2: Taking Example 3 as the control group, the self-repairing emulsion was replaced by an aqueous polyurethane resin (BZ-7: Changzhou Baichang Coatings Technology Co., Ltd.), and the other processes were normal.

[0090] Comparative Example 3: Taking Example 3 as the control group, the mass ratio of composite silica to self-repairing emulsion in the protective coating is 2:55, and other processes are normal.

[0091] In the embodiment and the comparative example, the thickness of the stainless steel strip is 4 mm, the thickness of the stainless steel strip after cladding is 4.1 mm, and the thickness of the protective layer is 50 μm.

[0092] Sources of raw materials used (for demonstration purposes only):

[0093] Stainless steel raw materials: carbon 0.015%, silicon 0.64%, manganese 0.44%, phosphorus 0.006%, sulfur 0.003%, chromium 22.13%, nickel 18.1%, molybdenum 6.12%, copper 0.71%, nitrogen 0.2%, the balance is iron; FeCoNiCr (45-50µm): Jiangsu Wellary New Materials Co., Ltd.; polycarbonate diol A862100: (Alpha) Zhengzhou Alpha Chemical Co., Ltd.; hydroxyl-terminated polydimethylsiloxane C303004, N,N-dimethylformamide D111999, dibutyltin dilaurate D100274, isophorone diisocyanate I109582, dimethylolpropionic acid B104539, 2,2'-diaminodiphenyl disulfide A10181 6. Hydroxyethyl methacrylate H434293, 1-thioglycerol T141418, 2-hydroxy-2-methylpropiophenone H110280, nano-silica S433693, 3-aminopropyltriethoxysilane A107147, micro-silica S104574, γ-glycidyloxypropyltrimethoxysilane G107576, dimethyl sulfoxide D106263, 3-fluoro-4-carboxyphenylboronic acid C120100, l-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride E106172, N-hydroxysuccinimide H109330, triethylamine T103285: Aladdin reagent; n-hexane, ethanol, ammonia water, analytical grade: Sinopharm Chemical Reagent Co., Ltd.

[0094] Performance Test:

[0095] The stainless steel strips prepared in the embodiments and comparative examples were subjected to performance tests;

[0096] Water contact angle: Use a surface contact angle tester to test with a 2μL deionized water droplet;

[0097] Self-healing rate: Draw a scratch with a length of 1 mm, a width of 3 µm, and a thickness of 25 µm on the surface, keep it at 30 °C for 12 h, and observe the length of the scratch. The self-healing rate = (L0-L1) / L0×100%, where L0 is the initial length of the scratch and L1 is the length of the scratch after keeping it warm.

[0098] Abrasion resistance: Use 800-grit sandpaper, place the sample on its surface, and then place a 50g weight on it to press it down. Apply a force to make the sample move horizontally on the sandpaper. After moving 20cm, rotate the sample 90° and move it horizontally 20cm. This is a cycle. Repeat 10 cycles to characterize the surface contact angle. If the contact angle change rate is within 2%, it is excellent, otherwise it is unqualified.

[0099] Corrosion resistance: After soaking in 10% NaCl solution for 24 hours, observe the surface corrosion morphology. If there is no discoloration or rust, it is qualified, otherwise it is unqualified. The results are shown in Table 1.

[0100] Table 1

[0101]

[0102] The present invention provides a high-flatness stainless steel strip for automobile decoration and a preparation process thereof. Through process adjustment and component design, a wear-resistant and corrosion-resistant high-flatness stainless steel strip for automobile decoration with a self-repairing super-hydrophobic surface is prepared. In Table 1, / indicates that the item has not been tested.

[0103] In order to give the stainless steel strip excellent resistance to mechanical damage, a protective coating prepared by blending a self-healing emulsion and composite silica is coated on the surface of the pretreated stainless steel strip to construct a super-hydrophobic, wear-resistant and corrosion-resistant protective layer.

[0104] Example 3 is compared with Comparative Example 1. In the present invention, silicon dioxide with the advantages of stable chemical properties, acid resistance, alkali resistance, high temperature resistance, etc. is introduced as a filler for the protective coating. In order to give the protective layer super-hydrophobicity, a super-hydrophobic surface is jointly constructed by constructing a micro-nano multi-scale rough structure and combining low surface energy modification. The nano-silica is coated and modified by 3-aminopropyltriethoxysilane to obtain amino-dense nano-silica. The micron-silica particles are coated and modified by γ-glycidyloxypropyltrimethoxysilane to obtain epoxidized micron-silica. Through an amino-epoxy reaction, particles of different sizes are assembled by chemical bonding to obtain strawberry-shaped silica. The amino groups on the surface of the strawberry-shaped silica are further introduced by phenylboronic acid groups and fluorine groups through an amidation reaction to construct multi-dimensional hydrophobic silica at the micro-nano scale, which is introduced into the protective coating to greatly improve the thermal stability and corrosion resistance of the coating.

[0105] Example 3 is compared with Comparative Example 2, wherein the self-repairing emulsion uses polycarbonate diol, hydroxyl-terminated polydimethylsiloxane, and isophorone diisocyanate as raw materials, and synthesizes a side chain-containing silicone prepolymer under the action of a catalyst, thereby improving the water resistance and thermal stability of the self-repairing emulsion, using dihydroxymethylpropionic acid as a hydrophilic chain extender, and further extending the chain with 2,2'-diaminodiphenyl disulfide, introducing a dynamic disulfide bond, and giving it self-repairing properties, and then using hydroxyethyl methacrylate as a capping agent to obtain a double-bond-terminated polyurethane, and then utilizing a thiol-double bond photoclick reaction to graft 1-thioglycerol onto the double-bond-terminated polyurethane to obtain a dihydroxy-terminated polyurethane, and then adding water for emulsification to obtain a self-repairing emulsion, thereby improving various properties of the protective layer.

[0106] Comparing Example 3 with Comparative Example 3, the phenylboronic acid groups on the surface of the composite silica and the dihydroxyl groups in the dihydroxy-terminated polyurethane can form reversible borate ester bonds, undergo chemical bonding, produce a synergistic effect, and increase the crosslinking density, thereby further improving its self-repair rate and thermal stability, constructing a complex self-repairing network system, and further improving the corrosion resistance and wear resistance of the protective layer.

[0107] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A process for preparing a highly flat stainless steel strip for automobile decoration. It is characterized in that The following steps are involved: S1: Stainless steel raw materials are put into a vacuum furnace for melting, and hot rolling, annealing, pickling, rolling, flattening and finishing are performed in sequence to form a stainless steel strip; S2: FeCoNiCr is selected as the cladding material and laser cladding treatment is performed to obtain a clad stainless steel strip; S3: frosting, polishing, cleaning, and drying the clad stainless steel strip in sequence, and then ion nitrocarburizing, cleaning, and drying to obtain a pretreated stainless steel strip; S4: Preparation of protective coating using self-healing emulsion and composite silica; S5: coating the protective coating on the surface of the pretreated stainless steel strip to form a protective layer, thereby obtaining a highly flat stainless steel strip for automobile decoration; The mass ratio of the composite silica to the self-healing emulsion in the protective coating is (3-5):55; The preparation of the self-repairing emulsion comprises the following steps: Under nitrogen protection, polycarbonate diol, hydroxyl-terminated polydimethylsiloxane, N,N-dimethylformamide, and dibutyltin dilaurate are mixed, the temperature is raised to 78-82°C, isophorone diisocyanate is added, the temperature is kept for 2-3 hours, a mixed solution of dihydroxymethylpropionic acid and N,N-dimethylformamide is added, the temperature is kept for 2-3 hours, the temperature is lowered to 48-52°C, 2,2'-diaminodiphenyl disulfide and a mixed solution of N,N-dimethylformamide are added, the temperature is kept for 1-2 hours, hydroxyethyl methacrylate is added, the temperature is kept for 2-3 hours, 1-thioglycerol, 2-hydroxy-2-methylpropiophenone, and a mixed solution of N,N-dimethylformamide are added, ultraviolet irradiation is carried out, the mixture is precipitated in n-hexane for 3-5 times, triethylamine is added, and deionized water is added for emulsification for 1-2 hours to obtain a self-repairing emulsion; The preparation of the composite silicon dioxide comprises the following steps: 1) Mix nano-silica, ethanol, ammonia water, deionized water and 3-aminopropyltriethoxysilane, heat to 78-82°C and keep warm for 4-5 hours, wash and dry to obtain amino-modified nano-silica; 2) Mix micronized silica, ethanol, ammonia water, deionized water and γ-glycidyloxypropyltrimethoxysilane, heat to 58-62°C and keep warm for 4-5 hours, wash and dry to obtain epoxidized micronized silica; 3) Mix amination nano-silica, epoxidized micro-silica, ethanol, ammonia water and deionized water, heat to 98-102°C and keep warm for 7-8 hours, wash and dry to obtain strawberry-shaped silica; 4) Mix strawberry-shaped silica and dimethyl sulfoxide, disperse them by ultrasonic for 20-30 min, add a mixed solution of 3-fluoro-4-carboxyphenylboric acid, l-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and dimethyl sulfoxide, keep warm at 18-25° C. for 3-4 h, centrifuge, wash and freeze-dry to obtain composite silica.

2. A process for preparing a highly flat stainless steel strip for automobile decoration according to claim 1, It is characterized in that The working conditions of annealing treatment are: heating to 950℃ and keeping warm for 25-35min.

3. A process for preparing a highly flat stainless steel strip for automobile decoration according to claim 1, It is characterized in that The working conditions of laser cladding treatment are: argon gas is used as the powder feeding gas source, the powder feeding amount is 11g / min, the laser power is 1.2kW, the scanning speed is 6mm / s, the circular spot diameter is 3mm, and the overlap rate is 50%.

4. The process for preparing a highly flat stainless steel strip for automobile decoration according to claim 1, It is characterized in that The working conditions of ion nitrocarburizing treatment are as follows: before heating to 300°C, a mixed gas of argon and methane with a volume ratio of 8:2 is introduced, ammonia is introduced when the temperature is raised from 300°C to 485°C, and ammonia, argon and methane with a volume ratio of 20:8:2 are introduced at 485°C; the holding temperature is 485°C and the holding time is 5h.

5. The process for preparing a highly flat stainless steel strip for automobile decoration according to claim 1, It is characterized in that In the preparation of the self-repairing emulsion, the working conditions of the ultraviolet irradiation treatment are: irradiation under ultraviolet light with a wavelength of 365nm for 3-4h.

6. A process for preparing a highly flat stainless steel strip for automobile decoration according to claim 1, It is characterized in that In the preparation of composite silica, the mass ratio of strawberry-shaped silica, 3-fluoro-4-carboxyphenylboric acid, and N-hydroxysuccinimide is 2.1:0.7:0.

8.

7. A highly flat stainless steel belt for automobile decoration. It is characterized in that The invention is prepared by the preparation process described in any one of claims 1 to 6.